Factors Influencing Earnings Management: Deferred Tax Liability, Tax Planning, and Company Size - Hanan Vania Amelinda; Cris Kuntadi (International Journal Labs, 2025)
This study examines the factors influencing earnings management, with a focus on deferred tax liability, tax planning, and company size. In a competitive business environment, companies strive to achieve optimal financial performance while minimizing tax liabilities, which often leads to earnings management practices. The research addresses three primary questions: the impact of deferred tax liability, tax planning, and company size on earnings management. Utilizing a qualitative approach and comprehensive literature review, this study analyzes relevant theories and empirical findings from various sources, including Mendeley and Google Scholar. The results suggest that deferred tax liability and tax planning significantly affect earnings management. Larger companies are more likely to engage in such practices due to greater resources and heightened investor expectations. Nonetheless, some studies present contradictory evidence, underscoring the complexity of these relationships. This research contributes to the tax accounting literature by synthesizing existing knowledge and proposing hypotheses for future studies. It also identifies additional determinants of earnings management, such as managerial ownership, audit quality, and corporate governance. The findings hold implications for policymakers, regulators, and corporate managers, emphasizing the importance of transparency and ethical conduct in financial reporting. Further research is recommended to investigate other influencing variables and contextual differences across industries.